Effect of the number and position of nozzle holes on in- and near-nozzle dynamic characteristics of diesel injection. (15th June 2015) - Moon, Seoksu; Gao, Yuan; Park, Suhan; Wang, Jin; Kurimoto, Naoki; Nishijima, Yoshiaki
Highlights: We analyze in- and near-nozzle dynamics of single- and multi-hole diesel injectors. An X-ray imaging technique was applied for analysis of dynamic characteristics. Number of nozzle holes significantly changes the transient needle behavior. Near-nozzle flow characteristics are highly affected by the hole arrangement. Multi-hole nozzles generate turbulent initial flow with faster mixing at downstream. Abstract: Despite the fact that all modern diesel engines use multi-hole injectors, single-hole injectors are frequently used to understand the fundamental properties of high-pressure diesel injections due to their axisymmetric design of the injector nozzles. A multi-hole injector accommodates many holes around the nozzle axis to deliver adequate amount of fuel with small orifices. The off-axis arrangement of the multi-hole injectors significantly alters the inter- and near-nozzle flow patterns compared to those of the single-hole injectors. This study compares the transient needle motion and near-nozzle flow characteristics of the single- and multi-hole (3-hole and 6-hole) diesel injectors to understand how the difference in hole arrangement and number affects the initial flow development of the diesel injectors. A propagation-based X-ray phase-contrast imaging technique was applied to compare the transient needle motion and near-nozzle flow characteristics of the single- and multi-hole injectors. The comparisons were made by dividing the entire injection process by three sub-stages: opening-transient, quasi-steady and closing-transient.